Community Service Satisfaction Index Information System Using the Web-Based CSS Method (Community Satisfaction Survey) at Statistics Center in Tapaktuan - Salya Rater; Fardiansyah; Safrijah (Jurnal Inotera, 2021)
The Community Satisfaction Index (CSI) is data and information about the level of community satisfaction from quantitative and qualitative measurement results in obtaining services from public service administrators by comparing their expectations and needs. Public service providers, community service units are faced with many related things. This application system uses the Community Satisfaction Survey (CSS) method, which is an activity carried out using a questionnaire as a research instrument. Community satisfaction services held are not aimed at seeking profit but must prioritize service quality in accordance with the demands, expectations and needs of the people being served. Public service providers are faced with many things related to improving service quality through good performance and quality of product. And this public service dominates the related agencies. To measure the performance of public service units, elements / indicators are needed to provide an assessment of the performance results of public service units. This system is designed to find out the results of public service performance at the Central Statistics Agency (BPS) in Tapaktuan which is measured based on the unknown Public Service Satisfaction Index. The Community Satisfaction Index (CSI) system aims to determine the level of service performance in Tapaktuan Central Statistics Agency (BPS) in providing services to the community, as well as a vehicle for absorbing community aspirations in the form of suggestions, hopes, as well as complaints about the services that have been provided so far. to be used as guidelines for policy makers, programs and strategies for improving services. One of the efforts to improve the quality of public services as mandated in the Republic of Indonesia Law Number 25 year 2000 concerning the National Development Program, in the Decree of the Minister of State Apparatus Empowerment Number 14 of 2017 concerning guidelines for preparing community satisfaction surveys of public service administration units.